Strategic performance management for soccer clubs: A quantitative model proposal - Coskun, A.; Dinc, M. S.; Tetik, S. (Journal of Human Sport & Exercise, 2021)
Soccer has been a very popular sports industry all over the world. Since soccer clubs generate a huge income from a variety of sources, the stakeholders of the soccer industry have come to recognize that this business should be managed professionally, and this would entail all of the functions of management, including performance management. This study provides a comprehensive framework for the strategic performance management of soccer clubs. In order to be strategy-focused, to better serve their mission, and to improve their performance, the performance management systems of soccer clubs should be linked to their missions and visions. Therefore, this study elucidates the application of a strategic performance management tool, the balanced scorecard (BSC), to the different levels of soccer clubs such as giant, middle-level, and lower-level. The study also provides a quantitative BSC model as a case study.